Pencegahan Judi Online: Celah Pengawasan Sistem Dan Resistensi Budaya Hukum - Elifas, Brussel Lorenzo Josua; Asri, Dyah Permata Budi (CV. Green Publisher Indonesia, 2025)
This study examines the effectiveness of Indonesia’s online gambling website blocking policy by focusing on two main issues: the absence of clear internal oversight norms and the incompatibility of blocking strategies with legal culture and socio-economic realities. Normatively, the government’s authority to block online gambling content is granted under Law Number 11 of 2008 on Electronic Information and Transactions, as amended by Law Number 1 of 2024, particularly Article 40 paragraphs (2a) and (2b). However, this research finds that the lack of explicit and operational internal supervision mechanisms within the EIT Law and Government Regulation Number 71 of 2019 has created opportunities for abuse of power, weakened the principles of good governance, and increased the risk of corrupt practices. Furthermore, from a legal culture perspective, blocking policies are ineffective due to society’s permissive attitudes toward online gambling, low levels of digital legal literacy, and declining public trust in law enforcement. Economic vulnerability, unemployment, and income instability also drive communities to continue accessing online gambling platforms despite legal prohibitions. This study concludes that technical and repressive blocking measures alone are insufficient without strong internal oversight, legal culture development, and comprehensive socio-economic policies. A holistic approach is therefore essential to ensure that online gambling prevention policies are effective, fair, and consistent with the rule of law.